Implementasi QRIS sebagai Inovasi Pembayaran Digital pada UMKM di Desa Serbananti - Diska Najwa Andini; Finkan Nadia; Wafiyah Ningrum; Nurul Huda Prasetya (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
This study examines the implementation of the Quick Response Code Indonesian Standard (QRIS) as a digital payment innovation for Micro, Small, and Medium Enterprises (MSMEs) in Serbananti Village, Serdang Bedagai Regency. The background of this study is the low level of digital literacy and the still high level of cash transactions, which causes MSMEs to face obstacles in efficiency and market access. The purpose of this study is to explore the QRIS adoption process, identify the challenges faced, and assess its impact on increasing transactions and customer satisfaction. This study uses a descriptive qualitative method with observation, interviews, and direct coaching techniques for MSMEs. The research findings indicate that the implementation of QRIS through the OVO application has facilitated payment transactions, increased consumer trust, and expanded the market. However, there are obstacles that arise, such as inadequate internet infrastructure, limited device availability, low digital literacy levels, and negative views regarding discount fees (MDR). These results underscore the fact that the success of QRIS implementation depends not only on technology, but also on continuous education, infrastructure support, and incentive policies that support MSMEs.